Rutina reduz as alterações morfológicas no modelo experimental de mucosite intestinal induzida por 5-fluorouracil - Fideles, Lázaro de Sousa (2020)
Intestinal mucositis is an adverse effect commonly associated with 5-fluorouracil (5-FU), an antimetabolite chemotherapeutic agent used in cancer therapy. For rutin (RUT), a flavonoid extracted from Dimorphandra gardneriana, several pharmacological activities have been described, such as antioxidant and anti-inflammatory. In the present study, the objective was to evaluate the effect of RUT on experimental intestinal mucositis induced by 5-FU in Swiss mice. Swiss mice were randomly divided into groups: Saline, 5-FU, RUT-50 (50 mg / kg RUT), RUT-100 (100 mg / kg RUT), RUT-200 (200 mg / kg RUT), Celecoxib (CLX, 7.5 mg / kg of Celecoxib) and CLX + RUT-200 (CLX + 200 mg / kg of RUT). The weight of the mice was assessed daily. After mucositis induction (single administration of 450 mg / kg of 5-FU, intraperitoneally) and after 3 consecutive days of treatment, the animals were euthanized and segments of the small intestine were collected for histopathological and morphometric evaluation, malondialdehyde (MDA), myeloperoxidase (MPO), Glutathione (GSH), mast cell and goblet cell count, immunohistochemistry for cyclooxygenase 2 (COX-2). Molecular docking was also carried out for possible RUT sites of action. 5-FU induced intense weight loss and reduced villus height compared to the saline group. Treatment with RUT decreased the histopathological changes induced by 5-FU and decreased the level of oxidative stress, decreasing the levels of MDA and increasing the concentration of GSH. RUT attenuated the inflammatory process, decreasing MPO activity, intestinal mastocytosis and COX-2 expression. Our findings suggest that the flavonoid RUT reverses the morphofunctional changes induced by 5-FU and has as a possible mechanism of action the COX-2 pathway.